EFFECTS OF 6 WEEKS YOGIC TRAINING ON SELECTED ANTHROPOMETRIC AND BODY COMPOSITION VARIABLES OF FEMALE UNIVERSITY LEVEL STUDENTS (International Journal of Food and Nutritional Sciences, 2022)
The practice of Yoga, according to Yogic scriptures, leads to the union of individual consciousness with universal consciousness. Yoga takes a holistic approach to everyone, considering their physical, mental, spiritual, and social well-being. Yoga practice beneficial for promotion of good health and mental well-being of the children and helps them to adopt with the changing environment. The present study has been designed to find out the effects of six weeks of yogic training on selected anthropometric and body composition variables of female university level students. Twenty-one healthy female university students from Guru Ghasidas Vishwavidyalaya age ranged 18 to 26 years were selected. Yoga practice was planned as 90 min/d, 06 d/week for 6 weeks. Height, Body weight, Resting Metabolism, BMI, Visceral Fat percentage, Body Age, and Whole-Body Fat percentage were recorded to compare pre- and post-camp parameters. All the selected variables Height, Body weight (Sig. 2-tailed-.000), Resting Metabolism (Sig. 2-tailed-.000), BMI (Sig. 2-tailed-.000), Visceral Fat percentage (Sig. 2-tailed-.000), Body Age (Sig. 2-tailed-.000), and Whole-Body Fat percentage (Sig. 2-tailed-.034) found significance difference except Height. So yogic training may be suggested to improves selected anthropometric and body composition functions of females except Height and it may predict due to the short-term training program.